The Work of Art in the Age of Armed Conflict in Central America (Global Journal of Human-Social Science, 2023)
The article interprets the artistic production of the seventies and eighties of the 20th century in Central America as a result of the alterations and conflicts generated by the cold war Likewise the text explains the constraints on the strategies of representation and the very notion of a work of art as a result of the political-military conflict generated by the struggles for revolutionary transformation in the region and finally the text lists and manifests some of the aesthetic and artistic contributions of the visual representations of the time of conflict to the emerging Central American art of the nineties and of the new century
Keywords: central american art; resistance art; the work of art in the age of armed conflict; displeasure images